Estimation of Air Pollutant Emissions in Eastern Indonesia from Non-Oil and Gas Sources (Case Study in Sulawesi and Papua) - Dessy Gusnita; Dita Fatria (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
Estimation of air pollutant emissions from non-oil and gas sources in eastern Indonesia, namely Sulawesi and Papua provinces during the period 2014 – 2016 was conducted. This paper intended to estimate the emission of three air pollutants namely NOx, SO2 and CO2. The aim was to find out the amount of pollutant and greenhouse gas (GHG) emissions in the Sulawesi and Papua regions. The method used was the emission estimation method based on statistical data of Gross Regional Domestic Income (GRDP) in the Papua and Sulawesi regions. The results from estimation of pollutant emissions was then carried out for pollutant emissions mapping. The pollutant emission estimation showed the emission of air pollutants in Sulawesi region was higher than Papua. The mapping of emissions in Sulawesi were consisted of four provinces, namely north, central, south and southeast Sulawesi. The Papua region were consisted of Papua and west Papua provinces. The highest emission in Sulawesi region was south Sulawesi. The CO2 emission in Sulawesi was increase about 23% with the detail value; 84.4 tons in 2014; 94.3 tons in 2015; and 103.7 tons in 2016. The emission of NOx during 2014 until 2016 are 0.53, 0.58 and 0.64 tons, there was an increasing in the emission of NOx around 21%. In addition, SO2 emission of south Sulawesi are 0.42 tons in 2014, 0.47 tons in 2015 and 0.51 tons in 2016, increased about 21 % during the year 2014 - 2016. In the Papua region, the emission in Papua was higher than Papua Barat province. CO2 emissions in Papua during 2014 -2016 were 112, 124.8 and 144.99 tons, it means the CO2 was increased 29%. The emission of NOx during 2014-2016 were 0.70, 0.77 and 0.89 tons, increased around 27%. In addition, SO2 emission was increase 26% with the detail value; 0.56 tons in 2014; 0.61 tons in 2015 and 0.71 tons in 2016.